Edna Ferber's America - McGraw, Eliza R. L. (Book collections on Project MUSE., 2013)
From the 1910s to the 1950s, Edna Ferber (1885--1968) published a series of bestselling novels that made her one of Doubleday's highest-paid authors, earned her a Pulitzer Prize for Fiction in 1925, and transformed her into a literary celebrity. She hosted dinner parties covered by the New York Times, lunched at the Algonquin Round Table with Dorothy Parker and Alexander Woollcott, and collaborated with George S. Kaufman on hit plays such as Dinner at Eight and Stage Door. In Edna Ferber's America, Eliza McGraw provides the first in-depth critical study of the author's novels, exploring the.